The Effect of Thin Capitalization, Managerial Ownership, and Capital Intensity on Tax Aggressiveness - Latifa Safara Falih; Afridayani Afridayani (Universitas Pembangunan Nasional Veteran Jakarta, 2026)
This study aims to examine the effect of thin capitalization, managerial ownership, and capital intensity on tax aggressiveness. The study uses secondary data obtained from companies included in the LQ45 index listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The sampling technique employed was purposive sampling, resulting in 60 observations. Hypothesis testing in this study was conducted using multiple linear regression analysis. The results indicate that thin capitalization, managerial ownership, and capital intensity simultaneously have a positive and significant effect on tax aggressiveness. Partially, thin capitalization and capital intensity have a positive and significant effect on tax aggressiveness, while managerial ownership does not have a significant effect on tax aggressiveness.